Japanese Clause Relativization Strategy - Pradhana, Ngurah Indra; Udayana, I Nyoman; Artawa, Ketut; Purnawati, Ketut Widya (Randwick International of Social Science Journal, 2025)
This study is entitled Japanese Clause Relativization Strategy. The purpose of this study is to describe the structure, strategy, and previous functions of relative clauses in Japanese. The theory used in analyzing the formulation of problems related to relative clauses in this study refers to the theory developed by Dixon (2010) in his book entitled "Basic Linguistic Theory 2". This study summarizes the analysis in micro linguistics, namely syntax. Syntactically, the antecedent in the Japanese relative clause is positioned at the end. In Japanese relative clauses, there are no relative markers. Only antecedents that are attached directly to the predicate are part of the relative clause. The function of the relative clause is to explain nouns or noun phrases which in Japanese are called hishuushokumeishi. This research is included in qualitative research. The data analyzed in this study came from the media and publications from the site https://www.sukasuki.org/koran-sukasuki. This study produced several points, including that Japanese relative clauses precede the nouns that are described or known by the previous term. The basic structure of relative clauses in Japanese always begins with a clause that describes and ends with the noun being described. Antecedents in Japanese can be nouns, noun phrases, or particles such as no and koto. There are no conjunctions such as "yang" in Indonesian or "who/which" in English. In this study, pseudo-conjunctions such as ni kan suru and to iu were found. Predicates in Japanese relative clauses can be verbs, verbs conjugated with hojodoushi, nouns, and can also be adjectives.